Securitization of Public Policy and Pandemic: Taiwan’s Case Against Covid-19 - Kai-Chun Wang (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2021)
Taiwan’s relatively better performance in the early stages of the on-going COVID-19 pandemic can largely be accredited to the rapid mobilization of public resources and the fast restructuring of government agencies to meet the pandemic-fighting coordination demand, but these measures are only possible when a community adopts a serious attitude followed by serious actions achieved via securitization of the COVID-19 pandemic. This paper attempts to compare and contrast the securitization of pandemic response and management of Taiwan, the United States, and Japan to highlight the importance of how even developed states with equal or better health infrastructure than Taiwan, by contextualizing the pandemic into different security scenarios has resulted in the performance gap against COVID-19.